Efficacy of hydroxyurea on the rate of blood transfusion requirement and serum ferritin levels in β-thalassemia major - Singh, Sudesh; Saini, Ghanshyam; Gattoo, Imran Ahmad; Digra, Sanjeev Kumar; Bakshi, Saloni (International Journal of Contemporary Pediatrics, 2017)
Background: Objective: To evaluate the efficacy of hydroxyurea on the rate of blood transfusion requirement and serum ferritin levels in β-thalassemia major patients. Methods: Design: Comparative trial. Setting: In a tertiary care centre in North India over a period of one year from December 2012 to November 2013. Blood transfusion requirements and serum ferritin levels during ten months prior to the beginning of the study in the same patients were considered as controls. Techniques: This was a hospital based interventional study, and was conducted over a period of 10 months at thalassemia clinic in post graduate department of pediatrics at govt. medical college and hospital, Jammu. Patients of β-thalassemia major attending the clinic, which fulfilled the inclusion criteria were selected as cases as well as controls. An informed written consent was taken from the parents/guardian of the patients to ensure compliance and regular follow up. Results: The blood transfusion requirements were significantly decreased at 6 and 10 months after starting treatment as compared to previous 10 months. There was a significant decrease in serum ferritin levels also after starting the treatment. Conclusions: The demonstrable significant decrease in the transfusion requirements as well as improvement in laboratory parameters including serum ferritin levels after initiating treatment with oral hydroxyurea in β-thalassemia major patients apparently suggests that oral hydroxyurea may find place in the management of β-thalassemia major children. However larger trials are warranted to derive optimum dosing schedule and confirm its efficacy so that it can be incorporated into future management guidelines.